2005
DOI: 10.1055/s-2004-821041
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Short-Term Concentric vs. Eccentric Resistance Training on Single Muscle Fiber MHC Distribution in Humans

Abstract: The purpose of this investigation was to determine the effects of a concentric vs. eccentric resistance training program on single muscle fiber myosin heavy chain (MHC) adaptations in humans. Fifteen sedentary, healthy males were divided into three groups: concentric training (CTG) (n = 6, 24.2 +/- 1.7 y, 181 +/- 2 cm, 82.5 +/- 4.6 kg), eccentric training (ETG) (n = 6, 23.7 +/- 1.6 y, 178 +/- 3 cm, 90.4 +/- 6.1 kg), and control (CTL) (n = 3, 23 +/- 1.5 y, 181 +/- 2 cm, 97 +/- 13.2 kg). The subjects performed 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 23 publications
2
21
0
2
Order By: Relevance
“…The increases in maximal strength for the three test modes varied from 21 to 44% in the present study and are comparable to reports of increases ranging from 12 to 67% with other investigations using similar muscle actions during training (Dudley et al 1991b;BenSira et al 1995) or with manipulation of muscle action completion time (Young and Bilby 1993;Morrissey et al 1998;Gillies and Docherty 1999). Contrary to this, Raue et al (2005) found a signiWcant increase in CON 1 RM strength after 4 weeks of CON resistance training but no changes with ECC training. Unfortunately, this latter research did not perform an ECC strength test.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…The increases in maximal strength for the three test modes varied from 21 to 44% in the present study and are comparable to reports of increases ranging from 12 to 67% with other investigations using similar muscle actions during training (Dudley et al 1991b;BenSira et al 1995) or with manipulation of muscle action completion time (Young and Bilby 1993;Morrissey et al 1998;Gillies and Docherty 1999). Contrary to this, Raue et al (2005) found a signiWcant increase in CON 1 RM strength after 4 weeks of CON resistance training but no changes with ECC training. Unfortunately, this latter research did not perform an ECC strength test.…”
Section: Discussionsupporting
confidence: 87%
“…This Wnding is supported by research in our laboratory (Putman et al 2004) as well as by other investigators (Adams et al 1993;Sharman et al 2001;Williamson et al 2001). Conversely, Raue et al (2005) did not observe many changes in MHC content of single Wbres after 4 weeks of either CON only or ECC only resistance training. The alteration in MHC content observed in the present study may be related to a reduction in hybrid Wbres co-expressing multiple MHC isoforms, resulting in an increase in the proportion of Wbres expressing MHCIIa only (Williamson et al 2001;Putman et al 2004).…”
Section: Discussionsupporting
confidence: 71%
“…Following a review of titles and abstracts, 66 full text articles were reviewed. When exclusion criteria were applied, only 20 studies satisfied the criteria to be included in the review 27464748495051525354555657585960616263. The main reasons for exclusion were: eccentric and concentric exercises not performed separately (n = 26); potential crossover effect (n = 9); participants with clinical conditions enrolled (n = 4); not published in a peer-review journal (n = 1); age of the participants (n = 2); and insufficient or incomplete description of the parameters of training (n = 4).…”
Section: Resultsmentioning
confidence: 99%
“…The total number of repetitions per session was variable (10 to 80) depending on the study. In 17 studies, exercise was performed with an isokinetic device that allowed for the control of angular velocity 27474849505152535455565758596061. In two studies that used a dynamic device for training, spotters were used to isolate eccentric and concentric contractions (eg, the participant performed the eccentric part of the movement, and a spotter lifted the weight during the concentric part) 6263.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it has recently been reported that resistance training using concentric (CON) and ECC contractions, with greater ECC loading, produces specific adaptations for a stronger, faster muscle, as indicated by greater IIx myosin adenosine triphosphatase gene expression using primarily isokinetic protocols (11,35,42). These findings have been validated through enhanced performance in Olympic lifters who trained with loads that were between 10 and 30% above their CON 1 repetitions maximum (RMs) across 6 weeks (13).…”
Section: Introductionmentioning
confidence: 99%